Effects of climatic variation and reproductive trade‐offs vary by measure of reproductive effort in greater sage‐grouse. Issue 12 (22nd December 2014) - Caudill, Danny; Guttery, Michael R.; Bibles, Brent; Messmer, Terry A.; Caudill, Gretchen; Leone, Erin; Dahlgren, David K.; Chi, Renee
Abstract : Research on long‐lived iteroparous species has shown that reproductive success may increase with age, until the onset of senescence, and that prior reproductive success may influence current reproductive success. Such complex reproductive dynamics can complicate conservation strategies, especially for harvested species. Further complicating the matter is the fact that most studies of reproductive costs are only able to evaluate a single measure of reproductive effort. We systematically evaluated the effects of climatic variation and reproductive trade‐offs on multiple reproductive vital rates for greater sage‐grouse ( Centrocercus urophasianus ; sage‐grouse), a relatively long‐lived galliforme of conservation concern throughout western North America. Based on over a decade of field observations, we hypothesized that reproduction is influenced by previous reproductive success. We monitored hen reproductive activity from 1998 to 2010, and used generalized linear mixed models to assess effects of climate and previous reproductive success on subsequent reproductive success. Reproductive trade‐offs manifested as chronic effects on subsequent reproduction and were not apparent in all measures of subsequent reproduction. Neither nest initiation nor clutch size were found to be affected by climatic variables (either year t − 1 or t ) or previous reproductive success. However, both nest and brood success were affected by climatic variation and previous reproductive success. Nest success was highest in years with high spring snowpack, and was negatively related to previous brood success. Brood success was positively influenced by moisture in April, negatively associated with previous nest success, and positively influenced by previous brood success. Both positive and negative effects of previous reproduction on current year reproduction were observed, possibly indicating high levels of individual heterogeneity in female reproductive output. Our results support previous research in indicating that climatic variability may have significant negative impacts on reproductive rates.